EKSPOR IMPOR CV SENYUM INDONESIA - Anastasia Glenna Zerlinda; Angelica Yulita Wirawanto; Chintya Chandra Saputri; Cindia Vitko Mitrikasatata; Cynthia Margareta (AIBPM Publisher, 2018)
Nowadays, decoration is one of the most developing industry all over the world. People are starting to care about their house or office looks. In Indonesia itself, curtain also become one of the many people needs. Curtain intended for blocking the light and make a room athmosphere more comfortable. A comfortable room will make activities more fun and making a job done a lot faster. In Indonesia the curtain business also making a great income, because lots of cutrain cloth is imported from foreign countries. The company will pay a certain amount of tax when they imported the cloth used to make the curtain. Ocasionally curtain cloth is produced in Indonesia and also being exported to other country. The demand from certain country is very high in curtain and this a very good oportunity to export many products. Many curtain sellers in indonesia still importing their products from foreign country, therefore CV Senyum Indonesia is trying to produce an import quality curtain and hopefully can export their product to foreign countries. Keywords: Curtain, cloth, export.